Does the Mathematics Assessment Website Support Mathematical Problem Solving Ability? A Systematic Literature Review - Harisman Nizar; Zulkardi Zulkardi; Ratu Ilma Indra Putri; Budi Mulyono (LP. Ma'arif Janggan Magetan, 2026)
Mathematical problem-solving ability is a core competency in mathematics education and a central focus of competency-based assessment. With the rapid advancement of digital technology, assessment websites have increasingly been utilized to measure and support students’ problem-solving skills. However, systematic studies that synthesize their characteristics, approaches, and contributions remain limited. This study aims to systematically review the literature on the use of assessment websites in enhancing students’ mathematical problem-solving abilities. A Systematic Literature Review (SLR) was conducted following PRISMA guidelines. Relevant articles were retrieved from Google Scholar and Scopus using keywords related to assessment websites and mathematical problem-solving. The inclusion criteria focused on websites that provide mathematical problems and allow students to access their results. The selected studies were analyzed thematically to identify assessment types, key website features, problem-solving frameworks, and their contributions. The findings indicate that assessment websites effectively support students’ problem-solving abilities, particularly through the provision of non-routine problems and immediate feedback on students’ work. The predominant framework identified is Polya’s problem-solving stages. These findings highlight the importance of developing digital assessment platforms that foster authentic and sustainable problem-solving skills in mathematics education.